2012
DOI: 10.1136/heartjnl-2012-302717
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, indications and appropriateness of antiplatelet therapy in patients operated for acute aortic dissection: associations with bleeding complications and mortality

Abstract: The indication for immediate antiplatelet therapy in patients later operated for acute aortic dissection was weak or absent in the majority of cases. Patients with ongoing platelet inhibition had more bleeding complications. Dual antiplatelet therapy was associated with increased early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…[5][6][7] Consequently, massive intraoperative and postoperative bleeding is a feared complication associated with considerably elevated morbidity and mortality. 8,9 Since first described in 2001, 10 recombinant factor VIIa (rFVIIa) (Novoseven; Novo Nordisk A/S, Bagsvaerd, Denmark) has gained increasing use for treating refractory bleeding in the off-label setting of cardiothoracic surgery. Previous studies have reported that rFVIIa effectively reduces blood loss and the need for allogeneic blood transfusions in standard cardiac surgery 11,12 ; however, questions have been raised as to whether the prothrombotic properties of rFVIIa lead to an increased risk of thromboembolic complications when used in patients without hemophilia.…”
Section: See Editorial Commentary Page 1860mentioning
confidence: 99%
“…[5][6][7] Consequently, massive intraoperative and postoperative bleeding is a feared complication associated with considerably elevated morbidity and mortality. 8,9 Since first described in 2001, 10 recombinant factor VIIa (rFVIIa) (Novoseven; Novo Nordisk A/S, Bagsvaerd, Denmark) has gained increasing use for treating refractory bleeding in the off-label setting of cardiothoracic surgery. Previous studies have reported that rFVIIa effectively reduces blood loss and the need for allogeneic blood transfusions in standard cardiac surgery 11,12 ; however, questions have been raised as to whether the prothrombotic properties of rFVIIa lead to an increased risk of thromboembolic complications when used in patients without hemophilia.…”
Section: See Editorial Commentary Page 1860mentioning
confidence: 99%
“…Pre-operative aspirin intake has been associated with increased blood loss, especially with aspirin doses N 325 mg/day [59], although generally without any clinical significance [60]. Several studies showed that clopidogrel, when associated with aspirin, increases bleeding and transfusion requirements in patients undergoing CABG [61] or other invasive surgery [62,63]. Recent studies have tended to show that the more potent the platelet inhibition provided by P2Y12 inhibitors, the higher the risk of bleeding [22,23].…”
Section: Risk Factors For Bleeding Eventsmentioning
confidence: 99%
“…2 Dual antiplatelet therapy with aspirin and clopidogrel increases perioperative bleeding and mortality in this patient group. 2 The significance of treatment with the novel antiplatelet drugs in this context has not been reported.…”
Section: E55mentioning
confidence: 99%
“…However, the use of prasugrel is associated with greater postoperative bleeding than clopidogrel. 2,3 Whether or not prasugrel therapy increases the incidence of postoperative bleeding complications is unknown. There are few reports on the management of major bleeding in patients on prasugrel prior to surgery, and the reversal of prasugrelinduced platelet inhibition with platelet transfusion has not been reported.…”
Section: E55mentioning
confidence: 99%